The The Effect of Environmental, Social and Governance (ESG) Business Strategy on Tax Aggressiveness with Corporate Social Responsibility (CSR) as a Moderation Variable - Rustandi Rustandi; Etty Murwaningsari; Sistya Rachmawati (Cita Konsultindo Research Center, 2024)
The primary purpose of this research is to find out how environmental, social, and governance issues (ESG) affect both prospector and defender corporate strategies as well as tax aggressiveness in the Consumer Non-Cyclicals and Basic Material sectors. Corporate social responsibility (CSR) will be used as a moderating variable. The researchers conducted a study on a selection of companies listed on the Indonesia Stock Exchange that were vulnerable between 2019 and 2021. They used purposive sampling approaches and acquired a total of 74 companies as samples. This study employed a random effect model approach to analyse the structure of panel data. Companies using both Prosfector and Defender business strategies have a direct impact on their level of tax aggressiveness. Nevertheless, companies that adopt a prospector business strategy and practice corporate social responsibility (CSR) moderation may reduce their ability to engage in aggressive tax practices. Conversely, companies that follow a Defender business strategy and practice corporate social responsibility (CSR) moderation may enhance their ability to engage in aggressive tax practices. The use of aggressive tax reduction methods has a negative influence on a company's sustainability, leading to a decline in share prices. This is due to the unfavourable perception of investors, who view the company's recorded earnings as being small. The government incurs losses while engaging in aggressive tax avoidance activities, as these practices might diminish state revenues derived from the tax sector. These findings offer compelling evidence regarding the significance of information sharing, particularly in relation to corporate sustainability. This study enhances comprehension of corporate tax conduct and commercial tactics in emerging nations.